Oxygen vacancy enhanced ferroelectricity in BTO: SRO nanocomposite films - Lin, Jun Liang; He, Ri; Lu, Zengxing; Lu, Yi; Wang, Zhiming; Zhong, Zhicheng; Zhao, Xiang; Li, Run-Wei; Zhang, Zhi Dong; Wang, Zhan Jie (Acta materialia, 2020)
The enhancement of ferroelectric properties in lead-free ferroelectric is usually achieved by strain engineering. Here, we report a surprising polarization enhancement effect in an isostructural ferroelectric nanocomposite system composited by the ferroelectric material of BaTiO3 and metallic non-ferroelectric oxide of SrRuO3. BaTiO3:SrRuO3 (BTO:SRO) ferroelectric nanocomposite films with the volume ratio of nanogranular SRO ranging from 0 to 16% grown on the Nb-doped SrTiO3 (NSTO) single-crystal substrates by pulsed laser deposition (PLD) are investigated. Robust ferroelectric polarization is observed with a remanent polarization of about 40 μC/cm2, comparable to those found in Pb(ZrxTi1-x)O3 thin films. By combining X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), density functional theory (DFT) calculations, and phase-field simulation, a hypothesis has been proposed that the polarization enhancement may be mainly attributed to the accumulation of oxygen vacancies at the BTO/SRO interface rather than lattice mismatch strain. The novel mechanism of polarization enhancement opens new possibilities for designing future ferroelectric devices.